2003
DOI: 10.2214/ajr.181.4.1811025
|View full text |Cite
|
Sign up to set email alerts
|

Imaging-Guided Percutaneous Splenic Biopsy Using a 20- or 22-Gauge Cutting-Edge Core Biopsy Needle for the Diagnosis of Malignant Lymphoma

Abstract: Imaging-guided small-bore cutting-edge needle biopsy of splenic lesions is a safe procedure. In most patients with primary or recurrent lymphoma, the disease subtype can be diagnosed reliably.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
33
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 12 publications
4
33
0
6
Order By: Relevance
“…These results are similar to those published in the Western world, although in immunocompromised patients or in underdeveloped countries, infections are more frequent. 3,6,[8][9][10] Infections are the most common benign lesions, especially pyogenic abscesses and, less commonly, splenic tuberculosis. A far higher frequency of splenic tuberculosis has been reported in certain countries, such as India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those published in the Western world, although in immunocompromised patients or in underdeveloped countries, infections are more frequent. 3,6,[8][9][10] Infections are the most common benign lesions, especially pyogenic abscesses and, less commonly, splenic tuberculosis. A far higher frequency of splenic tuberculosis has been reported in certain countries, such as India.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, an increasing number of investigators have reported that USG core-needle biopsy (CNB) is safe and effective; however, these series comprised a limited number of patients. [4][5][6] A multicenter retrospective study was conducted to evaluate the experience of several centers in Spain in USG needle biopsy (FNA or CNB) of the spleen.…”
mentioning
confidence: 99%
“…Fine-needle aspiration (FNA) biopsies in the diagnosis of malignant lymphomas have been reported [18][19][20] . Core-needle biopsies were superior to FNA since histology is more reliable than cytology [21][22][23] . The use of CT guidance and improved histological diagnostic techniques have promoted the development of non-surgical sampling of tumor masses in almost any location [4,9] .…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of core needle biopsy in making a diagnosis is 88% or better in multiple series in the literature (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In a study by Muraca et al (4), the biopsy yield in pediatric patients with a focal splenic lesion was 83% with 18-21-gauge needles.…”
Section: Biopsymentioning
confidence: 99%
“…In a study by Muraca et al (4), the biopsy yield in pediatric patients with a focal splenic lesion was 83% with 18-21-gauge needles. In general, the success rate for making the diagnosis is lower with fine-needle aspiration (FNA) procedures (2,5).…”
Section: Biopsymentioning
confidence: 99%